Wet Extraction Process and Its Physicochemical Changes in Virgin Coconut Oil: Proses Ekstraksi Basah dan Perubahan Fisikokimia Minyak Kelapa Murni - Arisandhy, Andira; Wulandari, Nur; Budi, Faleh Setia (Indonesian Journal of Innovation Studies, 2024)
Background: Indonesia is a major exporter of virgin coconut oil (VCO), but global demand surpasses production. Optimizing extraction processes is crucial. Knowledge gap: While various extraction methods exist, the effect of specific parameters on VCO quality and yield needs systematic analysis. Aim: This review evaluates extraction methods to optimize VCO production, focusing on enzymatic and microbial fermentation. Results: From eight articles, enzymatic fermentation using alcalase at 60°C for 1.5 hours produced high-quality VCO (free fatty acids 0.19%, water content 0.04%, peroxide value 8.28 meq/kg) with the highest yield (98.25%). Microbial fermentation, though longer, also yielded good quality. Novelty: Alcalase enzymatic fermentation is more efficient than microbial methods. Implications: These findings can guide industrial optimization of VCO production to meet SNI 7381:2022 standards. Highlights: Enzymatic fermentation with alcalase at 60°C for 1.5 hours yields the highest VCO quality and yield. Microbial fermentation, while effective, requires longer extraction times for similar results. Optimal temperature and time significantly influence the quality and yield of VCO, meeting SNI 7381:2022 standards. Keywords: Correlation, Enzymatic, Fermentation, Temperature, Time